Komunitas An-Nadzir Di Jembatan Miring Kota Palopo (Studi Kajian Sosiologis Keagamaan) - Tenrijaya; Pada Agustang, Andi Tenri (Palita: Journal of Social Religion Research, 2025)
This study examines the socio-religious context of the An-Nadzir community in Jembatan Miring, Palopo City, including the factors that influence it and the responses from government authorities and religious leaders. Through a phenomenological approach within the framework of religious sociology, the research reveals that the local population generally accepts the An-Nadzir community despite its distinct religious practices and interpretations. Its existence is grounded in the principle of enforcing the Prophet’s Sunnah in daily life, emphasizing values such as self-awareness, exemplary conduct, tolerance, and mutual assistance. The community has successfully adapted to the local socio-cultural environment through various elements, including kinship, education, regional policies, the economy, and the natural surroundings. Several factors contribute to its continued presence, including strong kinship ties, economic integration, a tolerant social atmosphere, and support from local authorities. Although differences remain in ritual practices, such as prayer methods, call to prayer, and dress, the government and religious leaders view the community positively and accept it as part of the Islamic landscape. The study contributes to a deeper understanding of how religious diversity can coexist harmoniously and serve as a foundation for building inclusive and tolerant communities.